2011
DOI: 10.1007/s13197-011-0459-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic and hypolipidemic effect of Aloe vera L. in non-insulin dependent diabetics

Abstract: Ninety non-insulin dependent diabetic subjects were selected from Punjab Agricultural University and Civil hospitals of Ludhiana. The selected subjects were divided into three groups viz. Group I, II and III having thirty subjects each. The subjects of group I were not given any treatment. The subjects of group II and III were supplemented with 100 mg and 200 mg of Aloe vera L. gel powder respectively for a period of 3 months and supplementation was continued along with nutrition counselling for the next 3 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 12 publications
4
53
1
2
Order By: Relevance
“…It is revealed that it has conspicuous pharmacological activities such as antibacterial (Subramanian et al, 2006;Arunkumar and Muthuselvam, 2009;Saritha et al, 2010;Fani and Kohanteb, 2012;Nejatzadeh-Barandozi, 2013), antifungal (Bajwa et al, 2007;Rosca-Casian et al, 2007;Khaing, 2011;Sitara et al, 2011), antiviral (Zandi et al, 2007), antioxidant (Baradaran et al, 2013;Ray et al, 2013;Kang et al, 2014), cytotoxic (Jose et al, 2014;Shalabi et al, 2015), antidiabetic (Tanaka et al, 2006;Choudhary et al, 2014;Suleyman et al, 2014), anti-inflammatory (Vijayalakshmi et al, 2012;Bhattacharjee et al, 2014), antitumor (El-Shemy et al, 2010;Srihari et al, 2015), nephroprotective (Iftikhar et al, 2015;Virani et al, 2016), antiulcer (Borra et al, 2011) and anti-aging effects which can be used as a moisturizing agent to cure cardiovascular diseases as well as to enhance the immune system (Chatterjee et al, 2013). It is used as an herbal medicine since long time which contains more than 100 bioactive constituents.…”
Section: Issn: 2319-7706 Volume 6 Number 3 (2017) Pp 2152-2162mentioning
confidence: 99%
“…It is revealed that it has conspicuous pharmacological activities such as antibacterial (Subramanian et al, 2006;Arunkumar and Muthuselvam, 2009;Saritha et al, 2010;Fani and Kohanteb, 2012;Nejatzadeh-Barandozi, 2013), antifungal (Bajwa et al, 2007;Rosca-Casian et al, 2007;Khaing, 2011;Sitara et al, 2011), antiviral (Zandi et al, 2007), antioxidant (Baradaran et al, 2013;Ray et al, 2013;Kang et al, 2014), cytotoxic (Jose et al, 2014;Shalabi et al, 2015), antidiabetic (Tanaka et al, 2006;Choudhary et al, 2014;Suleyman et al, 2014), anti-inflammatory (Vijayalakshmi et al, 2012;Bhattacharjee et al, 2014), antitumor (El-Shemy et al, 2010;Srihari et al, 2015), nephroprotective (Iftikhar et al, 2015;Virani et al, 2016), antiulcer (Borra et al, 2011) and anti-aging effects which can be used as a moisturizing agent to cure cardiovascular diseases as well as to enhance the immune system (Chatterjee et al, 2013). It is used as an herbal medicine since long time which contains more than 100 bioactive constituents.…”
Section: Issn: 2319-7706 Volume 6 Number 3 (2017) Pp 2152-2162mentioning
confidence: 99%
“…A previous study also found that aloesin from aloe might induce adiponectin revelation in adipocytes and thus, might control blood glucose and lipids [22]. Recently, it was reported that aloe itself and/or a certain complex molecule from aloe possesses a significant function in controlling blood glucose and lipids [23,24].…”
Section: Discussionmentioning
confidence: 93%
“…Heydari et al (2006) also found that dietary counseling was effective. Balagopal et al (2008) and Choudhary (2010) reported that education intervention was useful in reducing obesity.There was a no significant reduction (p<0.01) in the mean values of BMI, MUAC and TSFT in the subjects of group I, II, and III. Vishwanathan (1991) also reported no change in body weight in normal weight NIDDM patients and non-significant decrease in obese subjects after dietary counseling.…”
Section: Resultsmentioning
confidence: 99%